Implementation of an Interprofessional Approach in the Management of Acute Respiratory Failure in the Emergency Unit at Grandmed Hospital, Lubuk Pakam in 2023 - Kangga Chandra Adi Surya (Institut Kesehatan Medistra Lubuk Pakam, 2025)
Acute respiratory failure (ARF) is a critical condition frequently encountered in Emergency Departments (EDs) and requires rapid and collaborative management. Although various clinical guidelines have recommended the use of technologies such as CPAP, HFNO, and non-invasive ventilation, their effectiveness heavily depends on the synergy of medical teams from different professional backgrounds. Interprofessional collaboration (IPC) has been shown to improve service quality, expedite clinical decision-making, and reduce medical errors. However, its implementation at the local hospital level—particularly in the ED of RSU Grandmed Lubuk Pakam—has not been extensively studied. This study aims to explore in depth how the interprofessional approach is applied in managing acute respiratory failure in the ED of RSU Grandmed Lubuk Pakam, as well as to identify the barriers and supporting factors. This research employed a qualitative descriptive design with a case study approach. Data were collected through in-depth interviews, non-participatory observations, and document reviews. Informants were selected purposively and consisted of physicians, nurses, respiratory therapists, and pharmacists. Data were analyzed using thematic analysis.The study revealed five main themes:(1) team coordination that occurs informally but is not yet based on formal SOPs;(2) overlapping perceptions of professional roles; (3) verbal communication that is undocumented and lacks structure; (4) barriers such as limited interprofessional training and unclear collaborative systems; and (5) supporting factors including strong interpersonal relationships and open leadership. The implementation of the interprofessional approach in managing ARF at RSU Grandmed’s ED has been functionally present but is not yet systemically optimized. Strengthening efforts through collaborative SOPs, interprofessional training, and structured communication systems are required to improve the quality of care for patients with acute respiratory failure